Carotid Intima–Media Thickness as a Surrogate of Sub-clinical Atherosclerosis in COPD: Cross-Sectional Findings from a Himalayan Tertiary Centre - Dr Aseem Sirkeck; Dr Shagun; Dr Malay Sarkar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Carotid intima–media thickness (CIMT) predicts myocardial infarction and stroke, yet COPD-specific data from low- and middle-income settings are sparse. Objectives: (i) Compare CIMT and carotid plaque prevalence between stable COPD patients and never-smoking controls; (ii) explore clinical determinants of CIMT within COPD. Methods: Forty-three spirometry-confirmed, exacerbation-free COPD patients and forty-one age-/sex-matched never-smokers underwent bilateral B-mode carotid ultrasound (7–11 MHz) between March 2019 and April 2020. Sub-clinical atherosclerosis was defined as CIMT > 0.8 mm and/or plaque ≥ 1.2 mm. Multivariable linear and logistic models assessed associations with COPD duration, smoking index and LDL-cholesterol. Results: Mean CIMT was markedly thicker in COPD (0.92 ± 0.18 mm left, 0.92 ± 0.20 mm right) compared with controls (0.54 ± 0.05 mm and 0.54 ± 0.03 mm; p < 0.001). Sub-clinical atherosclerosis occurred in 31/43 (72.1 %) COPD cases versus 3/41 (7.3 %) controls (adjusted OR = 39.6, 95 % CI 10.3–152). Every five-year increment in COPD duration was associated with a 0.06 mm rise in CIMT (p = 0.02). Smoking index and LDL-cholesterol remained independent predictors. Conclusions: Stable COPD confers a five-fold CIMT excess independent of classical risk factors, supporting routine carotid scanning to refine cardiovascular prevention in pulmonary clinics. Longitudinal studies should clarify whether aggressive lipid-lowering or anti-inflammatory therapy attenuates CIMT progression in this high-risk population.